ANALISIS PENGARUH PER, EPS, ROA DAN DER TERHADAP HARGA SAHAM PERUSAHAAN SUB SEKTOR MESIN DAN ALAT BERAT TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2015-2019 - James lBenyamin soeindoen; Tanjung Tambunan (Jurakunman (Jurnal Akuntansi dan Manajemen), 2021)
The stock price is a reflection of the performance of a company. If the stock price of a company is stable and tends to increase, it indicates that the company's performance is increasing. This research was conducted to determine the effect of PER, EPS, ROA and DER as independent variables on stock prices as the dependent variable. The population of this research is pharmaceutical companies listed on the Indonesia Stock Exchange and samples of financial reports for the years 2017-2019 for seven companies and a total sample of 21 audited financial reports. Based on the results of statistical tests, it is found that partially the independent variables to the dependent variable, PER and EPS variables have a significant effect on stock prices. Meanwhile, the ROA and DER variables have no influence on the stock price. Simultaneously, the four independent variables have a significant effect on the dependent variable. Keywords: PER, EPS, ROA, DER, Stock Price